2020
DOI: 10.1136/sextrans-2020-054511
|View full text |Cite
|
Sign up to set email alerts
|

An alarming high prevalence of resistance-associated mutations to macrolides and fluoroquinolones inMycoplasma genitaliumin Belgium: results from samples collected between 2015 and 2018

Abstract: ObjectivesThe number of reported cases of multiresistant Mycoplasma genitalium (MG) is increasing globally. The aim of this study was to estimate the prevalence of macrolide and possible fluoroquinolone resistance-associated mutations (RAMs) of MG in Belgium.MethodsThe study was performed retrospectively on two sets of MG-positive samples collected in Belgium between 2015 and 2018. The first set of samples originated from routine surveillance activities and the second set came from a cohort of men who have sex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
(2 reference statements)
3
31
1
1
Order By: Relevance
“…Limited data are available on the trends and factors associated with fluoroquinolone-resistant M. genitalium in MSM [18, 31], particularly asymptomatic MSM. This study analyses clinical samples obtained from the MnM study of M.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data are available on the trends and factors associated with fluoroquinolone-resistant M. genitalium in MSM [18, 31], particularly asymptomatic MSM. This study analyses clinical samples obtained from the MnM study of M.…”
Section: Introductionmentioning
confidence: 99%
“…MSM are a population who already experience high levels of macrolide-resistant M. genitalium, and any increase in fluoroquinolone resistance may result in dual-class-resistance strains, for which very limited treatment options are available [30]. Limited data are available on the trends and factors associated with fluoroquinolone-resistant M. genitalium in MSM [18,31], particularly asymptomatic MSM. This study analyses clinical samples obtained from the MnM study of M. genitalium in asymptomatic MSM [7], and aims to (i) determine the levels of fluoroquinolone and dual-class resistance in the cohort, (ii) explore any clinical and behavioural factor associations with fluoroquinolone resistance in M. genitalium, and (iii) determine the distribution of antibiotic resistance among M. genitalium mgpB sequence types (STs).…”
Section: Introductionmentioning
confidence: 99%
“…11 More recent studies have found a much higher prevalence of macrolide resistance in both countries (74% and 58%, respectively). 37,38 These limitations mean that the results should be viewed with caution and require further validation. The way that travel can disseminate AMR may also mean that for certain bacterial species, a threshold may only be effective if globally applied.…”
Section: Discussionmentioning
confidence: 99%
“…2 Treatment is challenging due to a narrow repertoire of susceptible antimicrobials and a rise of macrolide resistance (MR). Multiple studies [3][4][5] demonstrate a high prevalence of macrolide resistance-mediating mutations (MRMMs) in the 23S rRNA gene across clinical samples. Macrolide resistance in the United Kingdom is high, estimated at 41%, 6 but there is a wide range globally.…”
Section: Introductionmentioning
confidence: 99%